Penggunaan Video Pembelajaran bagi Anak Usia Dini dalam Pembelajaran Daring - Kurniawaty, Lia; Ristiani, Indri; Apriliani, Siti Reista Asih; Gustini, Gustini; Sa’diyah, Halim Mahtu; Rosdiana, Dian (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Online learning is the choice of educational services for early childhood during the pandemic. The purpose of PKM is to design, create and implement learning videos in online learning. The implementation method is carried out in three initial, core, and final stages. The results showed that the child has a high interest in learning activities and has a curious attitude towards the material presented. Parents' responses to the use of learning videos showed that out of 20 parents there were 90% agreeing with the use of learning videos and 10% disagreed. Parental feedback on the content in the learning video showed that 60% were very satisfied, 40% expressed satisfaction and 0% were dissatisfied. The conclusion states that online learning with learning videos shows the increasing ability of students as well as the satisfaction of parents to the implementation and presentation of content in each video.